Workshop Strategi Revolusioner Pembelajaran Modern Melalui Integrasi Teknologi Cerdas dan Platform Media Sosial bagi Pendidikan Generasi Digital - Hamu, Fransiskus Janu (Jurnal Suara Pengabdian 45, 2023)
Education in the current digital era demands the use of smart technology and social media platforms in the learning process to suit the character of the digital generation. However, the competence of lecturers in Indonesia in this regard is still limited. Therefore, the workshop "Revolutionary Strategies for Modern Learning Through the Integration of Smart Technology and Social Media Platforms for Digital Generation Education" is important to implement. This workshop aims to provide understanding and skills to 187 lecturers in implementing technology and social media for learning innovation for digital generation students. Workshop material includes smart technology trends, use of social media platforms, digital evaluation and assessment strategies, as well as discussion of challenges and opportunities for integrating technology and social media in digital era learning. Participants' enthusiasm was quite high and the evaluation results showed that 91% were interested in implementing modern learning strategies after the workshop.